Biodecolorization of Anthraquinone and Azo Dyes by Newly Isolated Indonesian White-Rot Fungi - Kharisma Panji Ramadhan; Sita Heris Anita; Maulida Oktaviani; Fahriya Puspita Sari; Raden Permana Budi Laksana; Oktan Dwi Nurhayat; Dede Heri Yuli Yanto (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Water pollution by dyes represents from dyestuff industry becomes an environmental concern. Finding new isolates capable of decolorizing these dyes is important. The study aimed to assess the new isolates of white-rot fungi (WRF) as decolorizing agent of anthraquinone and azo dyes. Decolorization assay were conducted in Agar plates and liquid medium. During the decolorization, laccase activities produced by the fungal strains were analyzed. Identification of the fungal strains were investigated using molecular DNA analysis. The results showed that isolates M3, H18, and GP1 were able to decolorize anthraquinone and azo dyes in Agar and liquid medium. Based on DNA analysis, isolates M3, H18, and GP1 have the similarity to Trametes sanguinea, Trametes polyzona, and Neofomitella guangxiensis, respectively. Among the fungi, T. polyzona H18 exhibited high decolorization ability (70–90%) to the dyes (100 mg/L) after 96-hours incubation. Laccase activity was fluctuated during the reactions with tendency to increase at the beginning until its peak, then decreased at the end of incubation. This study demonstrated the potential of the new isolates from Indonesia to decolorize anthraquinone and azo dyes. The results of the study can provide an alteranative for bioremediation agents of contaminated water by synthetic dyes.